Effect of Dolomite and NPK fertilizer on land Coal Mine Closure Of Plant Growth Rubber (Hevea brasiliensis) in Samarinda.: Pemanfaatan Ekstrak Minyak Sawit Mentah sebagai Sumber β Karoten Dalam Proses Pembuatan Kacang Goyang di Kabupaten Kutai Kartanegara - Purwati; Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2015)
The main results are oil crops such as crude palm oil (Crude Palm Oil). Crude palm oil is the result of non-oil export commodities large enough nowadays. In fact, if it were processed into oil derivatives will provide a greater positive impact. One that can be used as oil derivative is a producing β-carotene. Attempts to separate the source of β-carotene from crude palm oil is the solvent selected and by extraction. Results extract crude palm oil will be applied in the manufacture of peanut shake at Regency. A rocking nut snacks are becoming the hallmark of Regency. Nuts rocking has limited shelf life. Hopefully, by the administration of β-carotene rocking nuts will last longer, be more interesting and rich in pro-vitamin A. Keywords: extraction, separation, β-carotene, peanut shake, pro-vitamin A